2020
DOI: 10.1007/s10964-020-01323-w
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Parental Support and Adolescent Negative Mood in Daily Life: between-Person Heterogeneity in within-Person Processes

Abstract: Lack of parental support is related to more adolescent negative mood. However, little is known about how fluctuations of parental support relate to fluctuations of negative mood within adolescents in daily life. The current study aimed to elucidate these processes at a day to day micro-level and examined to which extent adolescents would differ in the association between perceived parental support and adolescent negative mood. The sample consisted of 242 Dutch adolescents (Mage = 13.82, 63.2% female) who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 53 publications
(82 reference statements)
4
45
0
Order By: Relevance
“…Boele et al, 2021;LoBraico et al, 2019;Timmons & Margolin, 2015). Some studies showed substantial effect heterogeneity between families in how interaction quality and adolescent well-being were linked (Borghuis et al, 2020;Chung et al, 2009Chung et al, , 2011Janssen et al, 2020;Timmons & Margolin, 2015). For instance, whereas some adolescents may respond quite strongly to parent-adolescent interactions, others may be unaffected (e.g., Janssen et al, 2020).…”
Section: Methods To Study Micro Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Boele et al, 2021;LoBraico et al, 2019;Timmons & Margolin, 2015). Some studies showed substantial effect heterogeneity between families in how interaction quality and adolescent well-being were linked (Borghuis et al, 2020;Chung et al, 2009Chung et al, , 2011Janssen et al, 2020;Timmons & Margolin, 2015). For instance, whereas some adolescents may respond quite strongly to parent-adolescent interactions, others may be unaffected (e.g., Janssen et al, 2020).…”
Section: Methods To Study Micro Processesmentioning
confidence: 99%
“…Some studies showed substantial effect heterogeneity between families in how interaction quality and adolescent well-being were linked (Borghuis et al, 2020;Chung et al, 2009Chung et al, , 2011Janssen et al, 2020;Timmons & Margolin, 2015). For instance, whereas some adolescents may respond quite strongly to parent-adolescent interactions, others may be unaffected (e.g., Janssen et al, 2020). Individual factors (i.e., gender, depressive symptoms) partially explain these differences (Chung et al, 2009;Janssen et al, 2020;Timmons & Margolin, 2015).…”
Section: Methods To Study Micro Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, autonomy supportive parenting is believed to instill a general sense of volitional functioning in children, making them more likely to approach peers, which in turn, might foster friendships and protect against the development of psychopathology (57). In addition, our study did not assess parenting behaviors with ESM, although an increasing number of studies have demonstrated the feasibility and usefulness of focusing on more micro-level parent-child processes (22,23). Research that considers both predictors and outcomes at the level of daily life (e.g., from both child and parent) not only allows for examining these micro-level processes in more detail, but also allow for assessing individual variation in within-person or withinfamily processes (71).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…The data stem from a larger “Grumpy or Depressed?” study, which aimed to assess whether daily mood profiles (i.e., variability in affect) would predict the risk for depression in adolescents in the long run as recent work has indicated that the short-term dynamics could be linked to long-term psychopathology (e.g., Maciejewski et al, 2019 ; for a description of the study, see, e.g., de Haan-Rietdijk et al, 2017 ; Janssen et al., 2020 ; van Roekel et al, 2019 ). Briefly, during three 7-day measurement bursts or “waves” (with approximately 3-month intervals in between), 250 Dutch adolescents (12 to 16 years old) completed up to eight questionnaires per day at random moments (median interval: 2.25 hours).…”
Section: Applicationmentioning
confidence: 99%